2007
DOI: 10.1194/jlr.m700020-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic, enlarged, and dysfunctional HDL in human PLTP/apoA-I double transgenic mice

Abstract: In low density lipoprotein receptor (LDLR)-deficient mice, overexpression of human plasma phospholipid transfer protein (PLTP) results in increased atherosclerosis. PLTP strongly decreases HDL levels and might alter the antiatherogenic properties of HDL particles. To study the potential interaction between human PLTP and apolipoprotein A-I (apoA-I), double transgenic animals (hPLTPtg/ hApoAItg) were compared with hApoAItg mice. PLTP activity was increased 4.5-fold. Plasma total cholesterol and phospholipid wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
2
12
1
Order By: Relevance
“…Higher activity of CETP would facilitate transfer of HDLcholesterol to ApoB-containing lipoproteins, reducing the amount of cholesterol in HDL, reducing HDL particle size and increasing their capacity to accept new cholesterol from cells even when ApoB-containing lipoproteins are removed. This is consistent with several reports that smaller particles are more active in cholesterol efflux [40,41], and our recent finding of a correlation between the ability of plasma to support cholesterol efflux and CETP concentration [12]. It is, however, inconsistent with findings that functionality of HDL particles formed as a result of inhibition of CETP was not impaired [42,43].…”
Section: Discussioncontrasting
confidence: 53%
“…Higher activity of CETP would facilitate transfer of HDLcholesterol to ApoB-containing lipoproteins, reducing the amount of cholesterol in HDL, reducing HDL particle size and increasing their capacity to accept new cholesterol from cells even when ApoB-containing lipoproteins are removed. This is consistent with several reports that smaller particles are more active in cholesterol efflux [40,41], and our recent finding of a correlation between the ability of plasma to support cholesterol efflux and CETP concentration [12]. It is, however, inconsistent with findings that functionality of HDL particles formed as a result of inhibition of CETP was not impaired [42,43].…”
Section: Discussioncontrasting
confidence: 53%
“…In the mutPLTP tg mice, the extent of atherosclerosis was comparable to that in the control littermates. In PLTP tg mice, however, increased atherosclerotic lesion sizes were found, consistent with earlier findings in mice overexpressing human PLTP (10,16). The presence of cholate in the diet has been shown to regulate PLTP gene expression in vivo by the nuclear farnesoid X receptor (FXR), because the PLTP promoter contains an FXR response element (35).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, plasma PLTP has been identified as an HDL conversion factor. It remodels HDL to generate large particles and small lipid-poor preb-HDL (8)(9)(10). In vitro, HDL conversion depends on phospholipid transfer activity of PLTP (11).…”
mentioning
confidence: 99%
“…30 It has also been shown that RCT is less efficient in transgenic mice overexpressing PLTP, which may indicate that elevated levels of PLTP may promote atherogenesis by the accumulation of cholesterol in the blood vessel wall. 31 PLTP activity can be monitored by phospholipid carrying capacity from VLDL and LDL to HDL. PLTP activity is strongly correlated with the concentration of triglycerides in plasma and triglyceride content in HDL particles; this is probably due to the increased ability of phospholipid binding by HDL particles rich in triglycerides.…”
Section: The Role Of Pltp and Cetp In Lipoprotein Metabolismmentioning
confidence: 99%